Curva dose-resposta do extrato lipofílico composto por clorofilas e carotenoides da microalga Scenedesmus obliquus: papel oxidativo e envolvimento da sinalização purinérgica - Silveira, Marcylene Vieira da (2023)
More and more innovative proposals based on bioactive compounds are being presented to the public. The use of microalgae, such as the species Scenedesmus obliquus, has played an interesting role in this regard through the exploration of their produced metabolites, such as chlorophyll pigments and carotenoids. In this sense, we sought to understand the action of a dose-response curve for toxicity to the lipophilic extract extracted from the microalga Scenedesmus obliquus (Control groups, 75 μg/kg, 150 μg/kg, 300 μg/kg, 450 μg/kg and 600 μg/kg of extract via gavage for 30 days) in physiological and biochemical parameters so that it is possible to apply the same in future research for the treatment of diseases. Physiological parameters were measured, such as the animals' weight, food intake and water consumption at the beginning, middle and end of the experiment. No decrease was observed in either nutrition or body weight. From the results obtained in the TBARS, ER, PSH, NPSH and GST assays, it was possible to conclude that there were no changes in the liver, pancreas, kidney, heart and serum that could be linked to the worsening in the oxidative parameters of the animals subjected to treatment, configuring a non-toxic character of the compound. Within research involving the purinergic system and the immune system, the activity of the NTPDase-1 (CD39) and ADA enzymes in lymphocytes was quantified, with the activity of the NTPDase-1 enzyme being reduced at doses of 75 μg/kg and 600 μg/kg, even if not significant in relation to the control group, however, still showing a scenario where the activity of the enzyme was altered for a reason that has not yet been clarified. In relation to the central nervous system (CNS), more specifically in the hippocampus, the expression of P2X7 and A1 receptors, in addition to the interleukins IL-1β, IL-6 and IL-10, was quantified using the Western Blot technique. In this protocol, a decrease in IL-1β expression was observed in relation to the control at all doses tested. Extracts are already being used in industry considering that extraction methods provide quality and certification of the compounds obtained through them. Paying attention to the characteristics of the molecules that make up a given lipophilic extract, it is possible to see that a large part of its chemical structure is formed by phenolic compounds, which are already known to have a high antioxidant character. Thus, the results found suggest that the lipophilic extract composed of chlorophylls and carotenoids extracted from the microalgae Scenedesmus obliquus, when analyzed using the parameters studied here, did not present toxicity. Therefore, it can be considered that it could be tested in the future as a complementary treatment in different protocols.